A novel approach in elucidating the interaction of ecology, biology and social (eco-bio-social) factors with serum metabolites and its pathway among polyps and colorectal cancer: a study protocol - Abu Bakar MF; Azmawati Mohammed Nawi; Chin, SF; Makpol SM (Penerbit Universiti Kebangsaan Malaysia, 2024)
The increasing number of colorectal cancer (CRC) incidences and mortality rates have caused an increasing burden on the healthcare system of the involved countries. This will impact the important economic components as a burden including direct medical care and non-medical costs and have caused productivity losses among patients and caregivers. Early diagnosis is important to help in reducing mortality rates of CRC and enhancing disease treatments. Besides genetic pathways, lifestyle imbalance and environmental factors also are reported as the main causes of CRC. However, most of the previous studies only focused on one factor at a time which limit the understanding of how these factors could be manipulated in the disease biomarkers finding. Hence, this study helps to build a novel protocol to provide a better insight into the effects of the ecology, biology, and social factors on the differential level of a polyp and CRC serum metabolites that could potentially be used to distinguish patients with polyp or CRC. The finding of the study could serve as a potential biomarker that could be used in the development of new screening tools to enhance early screening of polyps and CRC.